A new species of Stenochironomus Kieffer, 1919 from the Atlantic Rainforest in southern Brazil (Diptera: Chironomidae). Issue 1 (2nd January 2016) - Parise, André Geremia; de Pinho, Luiz Carlos
ABSTRACT: Stenochironomus falcifer sp. n. is described and figured based on the characters of a male adult. The species was collected in Malaise traps in the Serra Furada State Park (PAESF), in Santa Catarina State, southern Brazil. It can be separated from all other species of Stenochironomus Kieffer, 1919 by its unique thorax pigmentation, with two dark patches on the lateral vittae, brownish postnotum and dark stripes on the scutum, and also by the combination of a narrow, parallel-sided anal point, inferior volsella with a stout apical seta, rounded posterior margin of the tergite IX and green metallic eyes. http://zoobank.org/urn:lsid:zoobank.org:act:3646E02D-7E3F-487A-BED1-A7937AFF8040